Features of the Expression of Second-Type Melatonin Receptors by Esophagus Epiteliocytes in Gastroesophageal Reflux Disease - O. A. Karpovich; T. T. Shtabinskaya; V. I. Shishko; Ya. A. Kolodzeysky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To investigate the specific features of the expression of second-type melatonin receptors (MTNR1B) by epithelial cells of the distal esophagus in gastroesophageal reflux disease (GERD), depending on the severity of endoscopic changes in the mucous membrane.Materials and methods. The study included 48 GERD patients, out of whom 37 and 11 people were suffering from non-erosive reflux disease (NERD) and erosive reflux disease (ERD), respectively. The control group consisted of 18 patients without GERD, comparable with the main groups by gender, age and body mass index. In order to determine the expression of MTNR1B, esophagogastroduodenoscopy with the collection of biopsy material from the mucous membrane of the distal esophagus was performed. The quantification of the MTNR1B expression intensity was carried out using the Aperio ImageScope_v9.1.19.1567 software. The level of melatonin metabolite, 6-sulphatehydroxymelatonin (6-SOMT), was determined in daily urine, as well as separately in daytime and nighttime portions.Results. The intensity of MTNR1B expression by esophageal epithelial cells in patients with NERD demonstrated no difference with the control group (0.436 (0.123, 0.668) and 0.437 (0.202, 0.692), respectively; p> 0.05). A significant decrease in the expression of MTNR1B receptors was noted in patients with ERD compared to NERD patients (0.127 (0.059, 0.156) and 0.436 (0.123, 0.668), respectively; p = 0.017) and patients in the control group (0.437 (0.202, 0.692); p = 0.033). The low intensity of MTNR1B expression was associated with more pronounced endoscopic changes in the mucous membrane of the esophagus (r = –0.40; p = 0.0015). A statistically significant relationship was found between the expression intensity of MTNR1B and the level of melatonin in the daytime (r = 0.42; p = 0.018), as well as the night/day index reflecting the daily rhythm of melatonin synthesis (r = –0.43; p = 0.016).Conclusions. The obtained data indicate that a decrease in the intensity of MTNR1B expression by esophageal epithelial cells can be considered as a prognostically unfavourable sign of the GERD course. The low intensity of MTNR1B expression is associated with a more severe (erosive) form of GERD and more pronounced endoscopic changes in the mucous membrane of the esophagus.